Design and thermoregulation of a new microextrusion dispense head for 3D‐plotting of thermally sensitive thermoplastics. Issue 2 (20th July 2012) - Ragaert, K.; De Baere, I.; Moerman, M.; Cardon, L.; Degrieck, J.
Abstract Three‐dimensional plotting of micro‐extruded filaments is a promising method for the manufacture of porous structures in thermoplastic polymers. However, it has been noted that conventional dispense head systems for this microextrusion are unsuitable for the reliable processing of thermally sensitive polymers like poly(lactic acid) (PLA): the batch polymer remains in the molten state prior to processing and it will degrade under this thermal load, leading to polymer chain reduction. Therefore, a new dispense head system was developed which thermally separates a cold material supply zone from the hot extrusion zone and allows for the processing of PLA‐based polymers without severe degradation. This manuscript discusses the design of the new dispense head and compares its thermoregulation with that of a conventional system by means of finite element modeling and infrared imaging. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers